Glyptothorax jayarami, a new species of catfish (Teleostei: Sisoridae) from Mizoram, northeastern India - Rameshori, Yumnam; Vishwanath, Waikhom (Zootaxa, 2012)
A new sisorid catfish, Glyptothorax jayarami, is described from the Kaladan basin of Mizoram, India. It is characteristicin having densely tuberculate skin; an elongate, ovoid thoracic adhesive apparatus with an oval central depression fromwhich the ridges on the apparatus diverge; two blackish-brown blotches at caudal-fin base behind the hypural plate; welldeveloped plicae on the ventral surfaces of simple and adjacent branched rays of pectoral and pelvic fins; a narrow caudal peduncle (5.5–7.9 % SL) and long 2 + 6–7 gill rakers on the first branchial arch.